Nitrogen Converters in Various Landfill Leachates - MERTOĞLU, BÜLENT; AKGÜL, DENİZ; BAKIRCI, KOZET (HARD, 2018)
Nitrogen has significant adverse effects on the environment and leads to operational failure in biological treatment units. Therefore, it is necessary to investigate and implement new nitrogen conversion pathways in order to expand alternatives for in-situ/ex-situ leachate treatment systems. In this study, microbial species responsible for nitrogen conversion were quantitatively investigated based on both phylogenetic and functional gene markers using real-time PCR in nine different leachate samples in Turkey. Real-time PCR studies revealed that landfill leachate harbored diverse nitrogen-converting microbial communities that include ammonia-oxidizing bacteria, nitrite-oxidizing bacteria, anammox bacteria, and ammonia-oxidizing archaea (AOA). Nitrosomonas and Nitrospira species were found to be the dominant ammonia-and nitrite-oxidizing bacteria, respectively. In contrast to the estimates, on average Nitrospira species were detected as 5 times more abundant than ammonia-oxidizing bacteria species. The presence of anammox and AOA revealed that partial nitrogen removal may occur inside landfills.
Keywords: ammonia-oxidizing archaea; anammox; landfill; leachate; nitrogen converter; SITU AMMONIA REMOVAL; COMPLETE NITRIFICATION; BIOREACTOR LANDFILL; NITRIFYING BACTERIA; DENITRIFICATION; QUANTIFICATION; RECIRCULATION; ORGANISMS; PHOSPHATE; COMMUNITY